2013
DOI: 10.4081/hpr.2013.714
|View full text |Cite
|
Sign up to set email alerts
|

The role of anxiety in binge eating behavior: a critical examination of theory and empirical literature

Abstract: The purpose of this manuscript is to expand the understanding of binge eating by reviewing the role of aspects of negative affect. Specifically, this paper will present evidence for further investigation of the bearing that anxiety may have in binge eating development and maintenance. A comprehensive review of the literature regarding the relation of binge eating and anxiety was performed. Valuable contributions have been made to the binge eating literature regarding some aspects of negative affect (i.e., depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 91 publications
(148 reference statements)
2
25
0
Order By: Relevance
“…Although mothers in our study were not clinically anxious (thus representative of a community sample), mothers who had higher than the average anxiety scores also had lower diet quality for their toddlers and themselves. Our findings are aligned with existing theories (Rosenbaum & White, ) and research suggesting that individuals may consume unhealthier foods to relieve anxiety symptoms (Paans et al, ; Pallister & Waller, ). In turn, individuals on diets low in micronutrients (DiGirolamo et al, ) or on high fat diets may display increased anxiety‐like behaviours (Sharma, Fernandes, & Fulton, ), illustrating a possible feedback loop among anxiety, food intake, and weight gain (Singh, ).…”
Section: Discussionsupporting
confidence: 89%
“…Although mothers in our study were not clinically anxious (thus representative of a community sample), mothers who had higher than the average anxiety scores also had lower diet quality for their toddlers and themselves. Our findings are aligned with existing theories (Rosenbaum & White, ) and research suggesting that individuals may consume unhealthier foods to relieve anxiety symptoms (Paans et al, ; Pallister & Waller, ). In turn, individuals on diets low in micronutrients (DiGirolamo et al, ) or on high fat diets may display increased anxiety‐like behaviours (Sharma, Fernandes, & Fulton, ), illustrating a possible feedback loop among anxiety, food intake, and weight gain (Singh, ).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, acute stress reaction, generalized anxiety disorder, and post‐traumatic stress disorder have been shown to increase the risk of dying, as well as of suicidal ideation and attempt . A possible mechanism may be that patients with severe FCR have increased stress owing to anxiety over trivial signs or symptoms, excessive time browsing websites to find information regarding their disease, especially the risk of relapse, as well as overly restrictive eating and other health behaviors . Increased stress could trigger such biological effects as reduced immunity .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have found that patients with obesity have increased risks of neuropsychiatric disorders, including anxiety and depression [1]. Meanwhile, patients with anxiety are more likely to seek palatable foods with higher carbohydrate and fat content, which predisposes them to obesity [2].…”
Section: Introductionmentioning
confidence: 99%